PENGARUH UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Dewi Kusuma Wardani; Julianti (Bajang Institute, 2022)
This study aims to determine the effect of firm size on tax avoidance with good corporate governance as a moderating variable. This study uses a population of mining companies listed on the Indonesia Stock Exchange (IDX). Sampling was done by purposive sampling method, namely taking samples with certain considerations and based on the interests and objectives of the study. This study uses multiple regression analysis techniques. The results of this study found that firm size did not have a positive effect on tax avoidance. Meanwhile, corporate governance can weaken the positive influence of firm size on tax avoidance